Eurípides, Phoenissae, ed. D. J. Mastronarde, Leipzig, Teubner Verlagsgesellschafts, 1988, II + 154 pp. ISBN 3-322-00461-9 (Minerva, 2019)
Review: Eurípides, Phoenissae, ed. D. J. Mastronarde, Leipzig, Teubner Verlagsgesellschafts, 1988, II + 154 pp. ISBN 3-322-00461-9